2005
DOI: 10.1093/molehr/gah133
|View full text |Cite
|
Sign up to set email alerts
|

Endometriotic cells are resistant to interferon-γ-induced cell growth inhibition and apoptosis: a possible mechanism involved in the pathogenesis of endometriosis

Abstract: In order to evaluate the involvement of cell proliferation and apoptosis in the pathogenesis of endometriosis, we investigated the effects of interferon-gamma (IFN-gamma) on cell growth inhibition and apoptosis of cultured ovarian endometriotic cyst stromal cells (ECSC), eutopic endometrial stromal cells with endometriosis (ESCwE) and normal endometrial stromal cells (NESC) by modified methylthiazoletetrazolium assay, 5-bromo-2'-deoxyuridine incorporation assay and internucleosomal DNA fragmentation assay. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 32 publications
2
64
0
3
Order By: Relevance
“…We have demonstrated that endometriotic cells, but not normal endometrial cells, are resistant to cytokine-induced apoptosis (20). It has also been demonstrated that endometrial apoptosis in the eutopic endometrium is lower in women with endometriosis than controls and is further decreased in the ectopic endometrium (8,10).…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…We have demonstrated that endometriotic cells, but not normal endometrial cells, are resistant to cytokine-induced apoptosis (20). It has also been demonstrated that endometrial apoptosis in the eutopic endometrium is lower in women with endometriosis than controls and is further decreased in the ectopic endometrium (8,10).…”
mentioning
confidence: 74%
“…Internucleosomal DNA fragmentation in ECSCs after BAY 11-7085 treatment was evaluated using a Quick Apoptotic DNA Ladder Detection Kit (BioVision Research Products, Mountain View, CA), as previously described (20). Cells (1 ϫ 10 7 ) of ECSCs were plated onto 100-mm culture dishes (Corning) in 10 ml of DMEM supplemented with 10% heat-inactivated FBS and cultured overnight.…”
Section: Assessment Of Cell Proliferation and Cell Viability Of Ecscsmentioning
confidence: 99%
See 3 more Smart Citations